2017
DOI: 10.1515/aucft-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Culture Medium for Lactobacillus bulgaricus using Box-Behnken Design

Abstract: Lactobacillus bulgaricus is a common yogurt starter in dairy production. But the viable counts of the bacteria in the productions are relatively low during free-drying and storage which is not good for its commercial production. In order to obtain a medium with high activity and high density for bacterial cultured, the experiments and regression analysis were conducted by.Box-Behnken design in this study, and a model was established to predict the influence of glucose (9- , which was very similar to the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…LAB has a limited capacity to synthesize amino acids and is therefore dependent on the use of exogenous nitrogen sources for optimal growth (Hebert et al, 2000; proteinase produced by Lactobacillus plantarum LP69 Espeche et al, 2009). Chen et al (2016) reported that glutamate, soybean peptone and casein hydrolysate can improve the viable cells number of Streptococcus thermophilus. There is a significant effect on Soya peptone to the growth of S. thermophilus and the optimum soya peptone content was 30g/L .…”
Section: Effect Of Nitrogen Source On L Plantarum Lp69 Producing Cepmentioning
confidence: 99%
“…LAB has a limited capacity to synthesize amino acids and is therefore dependent on the use of exogenous nitrogen sources for optimal growth (Hebert et al, 2000; proteinase produced by Lactobacillus plantarum LP69 Espeche et al, 2009). Chen et al (2016) reported that glutamate, soybean peptone and casein hydrolysate can improve the viable cells number of Streptococcus thermophilus. There is a significant effect on Soya peptone to the growth of S. thermophilus and the optimum soya peptone content was 30g/L .…”
Section: Effect Of Nitrogen Source On L Plantarum Lp69 Producing Cepmentioning
confidence: 99%
“…It is well known that many factors affect enzymatic activity in fruits and vegetables and which can be reducing the number of required essays (Yim et al, 2012). The RSM is widely used to optimize synthesis of bioactive molecules, extraction of desired compounds, and activity of enzymes (Yamaguchi et al, 2006;Zhang et al, 2017;Pramana et al, 2018). To the best of our knowledge, this work is the first study concerning the enzymatic activity optimization of the peroxidase extracted from the turnip.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology (RSM), also called the Box-Wilson methodology, is a useful tool to optimize the factors of fermentation processes by applying mathematics and statistics [23]. This technique is an experimental design based on the fit of a polynomial regression model for testing the multiple factors that influence the responses by varying the factors simultaneously, and fewer experiments are needed to study the effects of all factors [24,25]. Through RSM, the interaction effects of individual factors can also be determined.…”
Section: Introductionmentioning
confidence: 99%